A Client-Community Assessment of the NGO Sector in Uganda. - Barr, A; Fafchamps, M (2006)
Using original data from client-community assessments, we examine motivations in the Ugandan NGO sector. In general, client-community satisfaction with NGO interventions is high, even though some NGO staff are viewed as unresponsive, underskilled, or self-serving. We find evidence that NGOs endeavor to redress the balance between rich and poor, although more remote communities suffer neglect, possibly for cost reasons. NGOs are less inclined to maintain a permanent presence in more remote and poorer client-communities, which impacts negatively on their assessment scores. We also find evidence that NGOs too often operate in the same location, resulting in some duplication of effort. Finally, results indicate that community participation enhances satisfaction.